The impact of infrastructure on trade in Malaysia - Nor Asma Ahmad; Azila Jaini; Zaminor Zamzamir@Zamzamin (Vol. 3, Issue 2, pp. 42 - 49. December, 2015, 2015)
This study examines the role of infrastructure on trade in Malaysia from 1980 to 2013. The main objective is to test the addition of infrastructure into the augmented gravity equation and to examine the effects on trade through improvements in infrastructure. The impact of infrastructure on trade between Malaysia and 36 countries was examined using panel data analysis. The robustness of the results was tested by applying the pooled OLS, random effect model, and fixed effect model. The Hausman results offer support to the fixed effect model. The findings showed that all variables of infrastructures are significant and positive corresponding to the volume of trade between Malaysia and its trading partners.